Answer:
-70 is the correct answer
Answer:
Answer is C. Don't know what else there is to explain.
Step-by-step explanation:
It is in form (x,y) (ususally)
7.5 and 12
there is something called a coordinate system where a line called the y axis runs vertically for infinity and a line perpendicular to it, crosses it. the other line is called the x axis which also extends for infinity
the point where they cross is point (0,0) or the origin
basically the numbers tell you how far you are from the axises
on the y axis, + numbers are up and - numbers are down
on the x axis, + numbers are to the right and - numbers are to the left
7.5=x and 12=y
+7.5 is positive
7.5 means that the point is 7.5 units to the right of the origin in relation to the x axis
12 is positive
12 means that the point is 12 units up from the origin in relation to the y axis
hope this helped. feel free to ask if its too confusing
The simplified form of R(x) is ![R(x) =\frac{x^{2} -13x+42}{x^{2} -10x+25}](https://tex.z-dn.net/?f=R%28x%29%20%3D%5Cfrac%7Bx%5E%7B2%7D%20-13x%2B42%7D%7Bx%5E%7B2%7D%20-10x%2B25%7D)
<h3>Simplifying an expression </h3>
From the question, we are to simplify the expression
From the given information,
![f(x) =\frac{x^{2}-11x+28 }{x^{2}-11x+30}](https://tex.z-dn.net/?f=f%28x%29%20%3D%5Cfrac%7Bx%5E%7B2%7D-11x%2B28%20%7D%7Bx%5E%7B2%7D-11x%2B30%7D)
and
![g(x) =\frac{x^{2}-9x+20 }{x^{2}-12x+36}](https://tex.z-dn.net/?f=g%28x%29%20%3D%5Cfrac%7Bx%5E%7B2%7D-9x%2B20%20%7D%7Bx%5E%7B2%7D-12x%2B36%7D)
Also,
![R(x) = f(x) \div g(x)](https://tex.z-dn.net/?f=R%28x%29%20%3D%20f%28x%29%20%5Cdiv%20g%28x%29)
∴ ![R(x) =\frac{x^{2}-11x+28 }{x^{2}-11x+30} \div \frac{x^{2}-9x+20 }{x^{2}-12x+36}](https://tex.z-dn.net/?f=R%28x%29%20%3D%5Cfrac%7Bx%5E%7B2%7D-11x%2B28%20%7D%7Bx%5E%7B2%7D-11x%2B30%7D%20%5Cdiv%20%5Cfrac%7Bx%5E%7B2%7D-9x%2B20%20%7D%7Bx%5E%7B2%7D-12x%2B36%7D)
![R(x) =\frac{x^{2}-11x+28 }{x^{2}-11x+30} \times \frac{x^{2}-12x+36 }{x^{2}-9x+20}](https://tex.z-dn.net/?f=R%28x%29%20%3D%5Cfrac%7Bx%5E%7B2%7D-11x%2B28%20%7D%7Bx%5E%7B2%7D-11x%2B30%7D%20%5Ctimes%20%5Cfrac%7Bx%5E%7B2%7D-12x%2B36%20%7D%7Bx%5E%7B2%7D-9x%2B20%7D)
Factoring each of the quadratics
![R(x) =\frac{x^{2}-7x-4x+28 }{x^{2}-6x-5x+30} \times \frac{x^{2}-6x-6x+36 }{x^{2}-4x-5x+20}](https://tex.z-dn.net/?f=R%28x%29%20%3D%5Cfrac%7Bx%5E%7B2%7D-7x-4x%2B28%20%7D%7Bx%5E%7B2%7D-6x-5x%2B30%7D%20%5Ctimes%20%5Cfrac%7Bx%5E%7B2%7D-6x-6x%2B36%20%7D%7Bx%5E%7B2%7D-4x-5x%2B20%7D)
![R(x) =\frac{x(x-7)-4(x-7) }{x(x-6)-5(x-6)} \times \frac{x(x-6)-6(x-6) }{x(x-4)-5(x-4)}](https://tex.z-dn.net/?f=R%28x%29%20%3D%5Cfrac%7Bx%28x-7%29-4%28x-7%29%20%7D%7Bx%28x-6%29-5%28x-6%29%7D%20%5Ctimes%20%5Cfrac%7Bx%28x-6%29-6%28x-6%29%20%7D%7Bx%28x-4%29-5%28x-4%29%7D)
![R(x) =\frac{(x-4)(x-7)}{(x-5)(x-6)} \times \frac{(x-6)(x-6)}{(x-5)(x-4)}](https://tex.z-dn.net/?f=R%28x%29%20%3D%5Cfrac%7B%28x-4%29%28x-7%29%7D%7B%28x-5%29%28x-6%29%7D%20%5Ctimes%20%5Cfrac%7B%28x-6%29%28x-6%29%7D%7B%28x-5%29%28x-4%29%7D)
Simplifying
![R(x) =\frac{(x-7)}{(x-5)} \times \frac{(x-6)}{(x-5)}](https://tex.z-dn.net/?f=R%28x%29%20%3D%5Cfrac%7B%28x-7%29%7D%7B%28x-5%29%7D%20%5Ctimes%20%5Cfrac%7B%28x-6%29%7D%7B%28x-5%29%7D)
![R(x) =\frac{(x-7)(x-6)}{(x-5)(x-5)}](https://tex.z-dn.net/?f=R%28x%29%20%3D%5Cfrac%7B%28x-7%29%28x-6%29%7D%7B%28x-5%29%28x-5%29%7D)
![R(x) =\frac{x^{2} -6x-7x+42}{x^{2} -5x-5x+25}](https://tex.z-dn.net/?f=R%28x%29%20%3D%5Cfrac%7Bx%5E%7B2%7D%20-6x-7x%2B42%7D%7Bx%5E%7B2%7D%20-5x-5x%2B25%7D)
![R(x) =\frac{x^{2} -13x+42}{x^{2} -10x+25}](https://tex.z-dn.net/?f=R%28x%29%20%3D%5Cfrac%7Bx%5E%7B2%7D%20-13x%2B42%7D%7Bx%5E%7B2%7D%20-10x%2B25%7D)
Hence, the simplified form of R(x) is ![R(x) =\frac{x^{2} -13x+42}{x^{2} -10x+25}](https://tex.z-dn.net/?f=R%28x%29%20%3D%5Cfrac%7Bx%5E%7B2%7D%20-13x%2B42%7D%7Bx%5E%7B2%7D%20-10x%2B25%7D)
Learn more on Simplifying an expression here: brainly.com/question/1280754
#SPJ1